2009
DOI: 10.1002/ptr.2915
|View full text |Cite
|
Sign up to set email alerts
|

Effect of astragaloside IV on hepatic glucose‐regulating enzymes in diabetic mice induced by a high‐fat diet and streptozotocin

Abstract: Astragaloside IV exhibited a hypoglycemic effect in diabetic mice. The hypoglycemic effect of this compound may be explained, in part, by its inhibition of hepatic GP and G6Pase activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 31 publications
0
46
2
Order By: Relevance
“…antioxidation, [3][4][5] antivirus, 6,7) anti-apoptosis, 8,9) anti-hyperglycemic, 10,11) neuroprotection, 13) gastroprotection, 14) anti-chronicasthma, 15) and anti-lung-cancer. 16) One of AS-IV's targets is the cardiovascular system, and especially the heart.…”
mentioning
confidence: 99%
“…antioxidation, [3][4][5] antivirus, 6,7) anti-apoptosis, 8,9) anti-hyperglycemic, 10,11) neuroprotection, 13) gastroprotection, 14) anti-chronicasthma, 15) and anti-lung-cancer. 16) One of AS-IV's targets is the cardiovascular system, and especially the heart.…”
mentioning
confidence: 99%
“…This may be explained on the basis that astragaloside-IV has strong antioxidant ability (Gui et al, 2012). The lowering serum total cholesterol (TC) and triglycerides (TG) levels with astragaloside-IV were also reported in another study (Lv et al, 2010). Decrease in total protein level reflecting the liver and kidney injury caused by CCl 4 (Al-Yahya et al, 2013).…”
Section: Discussionmentioning
confidence: 71%
“…MPP + -induced neurodegeneration is specific to dopamine neurons and can be prevented by drug treatment with ginsenoside Rg1 or astragaloside IV (38,39). Recent studies have demonstrated that certain botanical extracts have an antioxidant effects against oxidative-stress induced damage and PD (38,40). Standardized extracts of ginsenoside Rg1 can efficiently terminate the toxic effects of MPTP in PD animal models (38).…”
Section: Discussionmentioning
confidence: 99%